The effect on ampacity for multiple cable crossing and mitigation to improve its ampacity - Radzi A.S.; Arifin N.A.N.; Anthony T.M.; Aida Z.; Azlina N.; Raj A.; Chakrabarty C.; Syaza N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cables; Computer software; Underground cables; Ampacity; Computer simulation technology (CST); High voltage cable; Localized heating; Medium voltage cables; Parallel configuration; Planning stages; Temperature rise; Crossings (pipe and cable)